Effectiveness of the Memory and Attention Battery in the Leiter-3 Scale in Diagnosing Attention Deficit and Hyperactivity Disorder (ADHD) - Abu Laban, Zain Akram; Thawabieh, Ahmad Mahmoud (Journal of Educational and Psychological Sciences, 2023)
This study aimed to verify the effectiveness of the memory and attention battery in the Leiter-3 scale in diagnosing attention deficit and hyperactivity disorder (ADHD), to identify the ability of the scale to differentiate between normal children and children with ADHD, and to determine if there are significant differences in the scale's ability to diagnose ADHD that are attributed to sex. The study used the descriptive method for its relevance to the study and its variables. The study individuals (100 children, aged 6–11) were chosen purposively; 50 of them were previously diagnosed as ADHD children by special education centers in Amman and academic support centers, while the other 50 were normal children; they were chosen from a public school (Alkaramah2 Basic School). The data was collected in the second semester of 2021-2022. To achieve the objectives of the study: The memory and attention battery in the Lieter-3 scale and the Gerisat (2007) ADHD Scale were used. The results of the study showed the effectiveness of the memory and attention battery in the Liter-3 scale in diagnosing ADHD and the ability of the scale to discriminate between ADHD children and normal ones. Finally, the results showed that there isn’t a statistically significant differences in the scale's effectiveness in diagnosing children that is attributed to sex. These results recommend using Litter-3 in diagnosing ADHD.
Keywords: Memory and Attention Battery; Liter-3 scale; Attention Deficit and Hyperactivity Disorder; Children